The Ratio of Acetate-to-Glucose Oxidation in Astrocytes from a Single (13)C NMR Spectrum of Cerebral Cortex - Marin-Valencia, Isaac (J Neurochem, 2014)
The (13)C labeling patterns in glutamate and glutamine from brain tissue are quite different after infusion of a mixture of (13)C-enriched glucose and acetate. Two processes contribute to this observation, oxidation of acetate by astrocytes but not neurons, and preferential incorporation of α-ketoglutarate into glutamate in neurons, and incorporation of α-ketoglutarate into glutamine in astrocytes. The acetate:glucose ratio, introduced previously for analysis of a single (13)C NMR spectrum, provides a useful index of acetate and glucose oxidation in the brain tissue. However, quantitation of relative substrate oxidation at the cell compartment level has not been reported. A simple mathematical method is presented to quantify the ratio of acetate to glucose oxidation in astrocytes, based on the standard assumption that neurons do not oxidize acetate. Mice were infused with [1,2-(13)C]acetate and [1,6-(13)C]glucose, and proton decoupled (13)C NMR spectra of cortex extracts were acquired. A fit of those spectra to the model indicated that (13)C-labeled acetate and glucose contributed approximately equally to acetyl-CoA (0.96) in astrocytes. Since this method relies on a single (13)C NMR spectrum, it can be readily applied to multiple physiologic and pathologic conditions.